The Roles of Bud-Site-Selection Proteins during Haploid Invasive Growth in Yeast - Cullen, Paul J. (The American Society for Cell Biology, 2002)
In haploid strains of Saccharomyces cerevisiae, glucose depletion causes invasive growth, a foraging response that requires a change in budding pattern from axial to unipolar-distal. To begin to address how glucose influences budding pattern in the haploid cell, we examined the roles of bud-site-selection proteins in invasive growth. We found that proteins required for bipolar budding in diploid cells were required for haploid invasive growth. In particular, the Bud8p protein, which marks and directs bud emergence to the distal pole of diploid cells, was localized to the distal pole of haploid cells. In response to glucose limitation, Bud8p was required for the localization of the incipient bud site marker Bud2p to the distal pole. Three of the four known proteins required for axial budding, Bud3p, Bud4p, and Axl2p, were expressed and localized appropriately in glucose-limiting conditions. However, a fourth axial budding determinant, Axl1p, was absent in filamentous cells, and its abundance was controlled by glucose availability and the protein kinase Snf1p. In the bud8 mutant in glucose-limiting conditions, apical growth and bud site selection were uncoupled processes. Finally, we report that diploid cells starved for glucose also initiate the filamentous growth response.